واقع الاستثمار في الطاقات المتجددة في الجزائر - عيجولي، عبدالله Aijouli, Abdullah; بن مسعود، آدم (جامعة ابن خلدون تيارت - الملحقة الجامعية قصر الشلالة, 2020)
تهدف هذه الورقة البحثية إلى التعرف على أبرز الإمكانيات المتاحة للجزائر من مصادر الطاقات المتجددة، بالإضافة إلى التطرق لواقع الاستثمار في هذا المجال، باعتبار أن الاستثمار في مجال الطاقات المتجددة قد برز في الآونة الأخيرة، كبديل استراتيجي للطاقات التقليدية (البترول والغاز)، خصوصا بعد انهيار أسعار البترول، بالإضافة لكون هاته الطاقات المتجددة تتميز بالاستدامة والتجدد من جهة، وكونها تحافظ على البيئة من جهة أخرى. This research paper aims to identify the Opportunities available to Algeria from the sources of renewable energies, in addition to examining the reality of investment in this field, considering that the investment in this field has emerged recently as a strategic alternative to traditional energies (oil and gas) especially after the collapse of oil prices, in addition to the fact that these energies are characterized by sustainability and renewal on the one hand, and preserve the environment on the other hand.
Keywords: الطاقة المتجددة -- الاستثمار الطاقوي -- التنمية المستدامة -- الجزائر